A review of exotic Kalanchoe taxa (Crassulaceae subfam. Kalanchooideae) naturalised and cultivated in Africa and the Gulf of Guinea islands, with their nomenclature updated - Smith, Gideon F. (Phytotaxa, 2023)
Data and information on exotic Kalanchoe taxa (Crassulaceae subfam. Kalanchooideae) provided in a range of floristic catalogues of regions and countries in Africa were collated and analysed to facilitate an improved understanding of the cultivation and invasion status of these taxa on the continent and the Gulf of Guinea islands. Overall, the inventory is expanded and brought up to date taxonomically and nomenclaturally. Results of the analysis are presented here as a series of tabulated inventories of the exotic Kalanchoe flora recorded for Africa. The exotic kalanchoes generally fall into two groups: (1) naturalised kalanchoes, and (2) cultivated kalanchoes. A total of 13 Kalanchoe taxa are recorded here as having become naturalised in Africa, with three, i.e., K. pinnata, K. prolifera, and K. tubiflora, especially widely, and with all three being invasive. Forty Kalanchoe taxa are recorded as being in cultivation, of which the potential spread of at least three, i.e., K. ×houghtonii, K. laetivirens, and K. scandens, apart from the three already naturalised, should be monitored and material eradicated. These three species all belong in K. [subg. Bryophyllum] sect. Invasores. The correct identification, early detection, and rapid eradication of established and emerging invasives are essential to facilitate the management of such species and to prevent their further spread.